Effect of different water stress with superabsorbent (S.A.P) treatment on growth of PB350 clone (Hevea brasiliensis) / Mohamad Ashraf Zaini - Zaini, Mohamad Ashraf (Faculty of Plantation and Agrotechnology, 2019)
Hevea brasiliensis, traditionally grown in humid tropics characterized by high year round rainfall. However, due to an increase in the world's demand for rubber, future plants in dry areas characterized by water will be established. This research gives a detail about the effect of different water stress with superabsorbent (S.A.P) treatment on growth of rubber clone at nursery stage. One clones from Malaysia Rubber Board (MRB), PB350 with 5 months was used in the study. Six treatment levels were used, irrigated plants (Every day, 3 days, 6 days), never irrigated which acted as control) and two treatment of superabsorbent polymer for Treatment 4 and 6. The experimental design was Completely Randomized Design (CRD) with four replications. A significant decrease in stress level was observed. Changes of plant growth such as plant height, number of leaves, dry weight of plant, and chlorophyll content showed that treatment with daily watered had higher values than other treatments. However, there is no significant different between treatment daily watered and applying superabsorbent polymer for 3 days withholding water. Treatment unable to adapt to water stress during treatments which never irrigated. By applying superabsorbent polymer on PB350 clones had responded to water stress by physiological responses. This indicated that superabsorbent polymer had positive effects on growth of rubber clone even under drought-stress conditions.